2018
DOI: 10.7150/jca.24887
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric Effects of Head and Neck Immobilization Devices on Multi-field Intensity Modulated Radiation Therapy for Nasopharyngeal Carcinoma

Abstract: Background: In practice, the dose perturbation effect of head and neck immobilization devices is often overlooked in intensity-modulated radiation therapy (IMRT) for nasopharyngeal carcinoma (NPC). Purpose of this study is to verify and analyze the dosimetric effect of head and neck immobilization devices on NPC multi-field IMRT.Methods: Ten patients with nasopharyngeal carcinoma were randomly selected. Two sets of body contours were established for each patient. One set of body contours did not contain the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Patient immobilization devices have become an important tool to guarantee the accurate delivery of highly conformal dose distributions [3]. As the materials used in immobilization devices are not completely X-ray transmissible and can cause attenuation of the delivered dose, the dosimetric effects of immobilization devices should be included in dose calculations [17,24]. Beam attenuation from the couch, additional inserts, and immobilization devices can cause a misrepresentation of the actual dose delivered to the PTV, with a deviation of more than the recommended 3-5% accuracy range reported by Olch [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patient immobilization devices have become an important tool to guarantee the accurate delivery of highly conformal dose distributions [3]. As the materials used in immobilization devices are not completely X-ray transmissible and can cause attenuation of the delivered dose, the dosimetric effects of immobilization devices should be included in dose calculations [17,24]. Beam attenuation from the couch, additional inserts, and immobilization devices can cause a misrepresentation of the actual dose delivered to the PTV, with a deviation of more than the recommended 3-5% accuracy range reported by Olch [3].…”
Section: Discussionmentioning
confidence: 99%
“…Beam attenuation from the couch, additional inserts, and immobilization devices can cause a misrepresentation of the actual dose delivered to the PTV, with a deviation of more than the recommended 3-5% accuracy range reported by Olch [3]. Chen reported the attenuation of head and neck immobilization devices, which reduced the dose coverage rate from 1.51 to 9.92% and the average dose from 0.93 to 1.92% of planning target volumes in nasopharyngeal carcinoma [24]. Olson assessed the dose variance from immobilization devices in volumetric-modulated arc therapy (VMAT) head and neck treatment planning and found that the plan calculated without immobilization devices was problematic, showing compromised V 95 , D 100 , and PTV coverage [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient immobilization devices have become an important tool to guarantee accurate delivery of highly conformal dose distribution (20). As the materials used in immobilization devices are not completely X-ray transmission and can cause attenuation of delivering dose, the dosimetric effects of immobilization devices should be included in dose calculations (14,21) . In addition, the bolus-effect cannot be avoided either.…”
Section: Discussionmentioning
confidence: 99%
“…Chen found the attenuation of the head and neck immobilization devices, which reduce dose coverage rate (reduced by from 1.51% to 9.92%) and average dose (reduced by from 0.93% to 1.92%) of planning target volumes in nasopharyngeal carcinoma (21). Alyssa Olson assessed dose variance from immobilization devices in VMAT head and neck treatment planning, and found that plan calculated without immobilization devices was problematic with compromising V95, D100 and PTV coverage (14).…”
Section: Discussionmentioning
confidence: 99%